Peran Hot Cognition, Primary Appraisal, dan Resilience dalam Hidup Manusia - Irene Prameswari Edwina (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2012)
Humans faced with a variety of stressful conditions that can cause strong stress, and then can interfere with the welfare of human life. In extreme cases it can cause people to experience psychopathology. Preventive efforts to avoid disruption due to strong stress is to develop the capacity of the human resilience. Resilience is the ability of an individual to be able to successfully adapt and function well in the stressful situations.Perception of stress depend on primary appraisal, the appraisal of the stressor as harm / loss, threat, or challenge a different appreciation of the human cause. Factors that can affect humans in assessing the stressor is hot cognition refers to the mental process which is driven by the desires and feelings. Humans play an active role in managing stress, and also have limited control of their environment, because it is n e c e s s a r y f o r h u m a n t o b e r e s i l i e n c e .Key words: hot cognition, primary appraisal, resilience